2015
DOI: 10.1007/s00425-015-2446-6
|View full text |Cite
|
Sign up to set email alerts
|

A novel cinnamyl alcohol dehydrogenase (CAD)-like reductase contributes to the structural diversity of monoterpenoid indole alkaloids in Rauvolfia

Abstract: Based on findings described herein, we contend that the reduction of vomilenine en route to antiarrhythmic ajmaline in planta might proceed via an alternative, novel sequence of biosynthetic steps. In the genus Rauvolfia, monoterpenoid indole alkaloids (MIAs) are formed via complex biosynthetic sequences. Despite the wealth of information about the biochemistry and molecular genetics underlying these processes, many reaction steps involving oxygenases and oxidoreductases are still elusive. Here, we describe mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…Accordingly, it is likely that overexpression of AaCAD ( Figure 3E ) enhances the catalytic conversion of artemisinin aldehyde to alcohol in the presence of NADPH in trichomes. In addition to our observations, CAD or CAD-like enzymes have been reported to be involved in the formation of monoterpenoid indole alkaloids in Rauvolfia serpentine ( Geissler et al, 2016 ). Moreover, additional biochemical studies have shown that CAD is characterized by a high promiscuity level of different substrates ( Chao et al, 2014 ; Geissler et al, 2016 ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Accordingly, it is likely that overexpression of AaCAD ( Figure 3E ) enhances the catalytic conversion of artemisinin aldehyde to alcohol in the presence of NADPH in trichomes. In addition to our observations, CAD or CAD-like enzymes have been reported to be involved in the formation of monoterpenoid indole alkaloids in Rauvolfia serpentine ( Geissler et al, 2016 ). Moreover, additional biochemical studies have shown that CAD is characterized by a high promiscuity level of different substrates ( Chao et al, 2014 ; Geissler et al, 2016 ).…”
Section: Discussionsupporting
confidence: 83%
“…In addition to our observations, CAD or CAD-like enzymes have been reported to be involved in the formation of monoterpenoid indole alkaloids in Rauvolfia serpentine ( Geissler et al, 2016 ). Moreover, additional biochemical studies have shown that CAD is characterized by a high promiscuity level of different substrates ( Chao et al, 2014 ; Geissler et al, 2016 ). Based on our and other reports, one hypothesis is that CAD-mediated crosstalk can occur in other metabolic pathways.…”
Section: Discussionsupporting
confidence: 83%
“…The upregulation of FDH (spot 6503) with the increase of exogenous BAP concentration might accelerate one‐carbon metabolism during tuber development. Perakine reductase‐like (spot 3408) and 8‐hydroxy geraniol dehydrogenase‐like (spots 4519 and 5504), participating in the biosynthesis of monoterpenoid indole alkaloids (Sun et al , Miettinen et al , Geissler et al ), were also upregulated with the increase of exogenous BAP concentrations. NADH‐cytochrome b5 reductase (CBR) serves as electron donor for cytochrome b5 (a ubiquitous electron carrier), thus participating in a variety of metabolic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Like all MIAs, ajmaline is produced via the versatile intermediate strictosidine, which is subject to multiple catalytic steps to yield the structurally diverse members of the MIA natural product family . All biosynthetic transformations leading from strictosidine to ajmaline have been detected in enzyme fractions from Rauwolfia cell culture, though only six biosynthetic genes have been cloned and characterized (Figure ) . Several studies showed that vomilenine is an ajmaline biosynthetic intermediate that is produced through selective hydroxylation of vinorine at the C‐21 position by Rauwolfia cell culture extracts (Figure ) .…”
Section: Figurementioning
confidence: 99%